Distributed denial‐of‐service attack mitigation in network functions virtualization‐based 5G networks using management and orchestration. (14th April 2021) - Köksal, Sarp; Dalveren, Yaser; Maiga, Bamoye; Kara, Ali
Summary: The fifth generation (5G) technology is expected to allow connectivity to billions of devices, known as Internet of Things (IoT). However, IoT devices will inevitably be the main target of various cyberattack types. The most common one is known as distributed denial‐of‐service (DDoS) attack. In order to mitigate such attacks, network functions virtualization (NFV) has a great potential to provide the benefit of elasticity and low‐cost solutions for protecting 5G networks. In this context, this study proposes a new mechanism developed to mitigate DDoS attacks in 5G NFV networks. The proposed mechanism utilizes intrusion prevention system's (IPS) virtual machines (VMs) to intercept the queries. Based on the volume of DDoS traffic, IPS's VMs are dynamically deployed by means of management and orchestration (MANO) in order to balance the load. To evaluate the effectiveness of the mechanism, experiments are conducted in a real 5G NFV environment built by using 5G NFV environment tools. To our best knowledge, this is the first time that NFV‐based mechanism is experimentally tested in a real 5G NFV environment for mitigating DDoS attacks in 5G networks. The experimental results verify that the proposed mechanism can mitigate DDoS attacks effectively. Abstract : In order to mitigate distributed denial‐of‐service attacks, this study proposes a new mechanism that utilizes intrusion prevention system's virtual machines to intercept the queries. Based on the volume of DDoS traffic, IPS's VMs are dynamically deployed by means of management and orchestration in order to balance the load. The experimental results verify that the proposed mechanism can mitigate DDoS attacks effectively, which is the first time that NFV‐based mechanism is experimentally tested in a real 5G NFV.